Virtual screenings of the bioactive constituents of tea, prickly chaff, catechu, lemon, black pepper, and synthetic compounds with the main protease (Mpro) and human angiotensin-converting enzyme 2 (ACE 2) of SARS-CoV-2 - Nazim Uddin Emon; Md. Munsur Alam; Irin Akter; Saima Akhter; Anjuman Ara Sneha; Md. Irtiza; Marufa Afroj; Arifa Munni; Masruba Hossen Chowdhury; Summiya Hossain (SpringerOpen, 2021)
Abstract Background COVID-19 has mutation capability, and there are no specific drug therapies that are available to fight or inhibit the proteins of this virus. The present study aims to investigate the binding affinity of the bioactive and synthetic compounds with the main protease (Mpro) enzymes and angiotensin-converting enzyme 2 (ACE 2) by computational approach. PASS prediction, pharmacokinetics, and toxicological properties prediction studies were performed through the Google PASS prediction and Swiss ADME/T website. Besides, molecular docking studies were accomplished by BIOVIA Discovery Studio 2020, UCSF Chimera, and PyRx autodock vina. Results The docking scores were inferred and the selected compounds showed results varying from −3.2 to −9.8 (kcal/mol). Theaflavin scored the highest docking score to the 5REB, 6VW1, and 1R42 enzymes and showed the binding affinity as −6.3 kcal/mol, −9.8 kcal/mol, and −8.6 kcal/mol, respectively. Again, kaempferol showed the best binding affinity to the 7BQY (−7.1 kcal/mol) and 6Y2FB (−6.6 kcal/mol) enzymes. All the chemical constituents showed better probability in action in pass prediction analysis. Besides, no ligands (except theaflavin) have any conflict with Lipinski's rules of five, which authorized the drug probability of these ligands. Conclusion Therefore, the selected compounds could be considered a potential herbal treatment source against SARS-CoV-2.